Hypokalemic Hypochloremic Metabolic Alkalosis in Cystic Fibrosis: A Retrospective Observational Study with Clinical Characterization, CFTR Genetic Profiling, and a Comparative Genetic Analysis with Patients from a Brazilian Reference Center - Andressa Oliveira Peixoto; Larissa Ferreira Selicani; Camila Bento Safi; Daniela Souza Paiva Borgli; Adyléia Aparecida Dalbo Contrera Toro; Nathália Mariana Santos Sansone; Andrea de Melo Alexandre Fraga; Fernando Augusto Lima Marson; José Dirceu Ribeiro (International Journal of Molecular Sciences, 2026)
Cystic fibrosis is a genetic disorder caused by pathogenic variants in the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) gene and may be complicated by hypokalemic hypochloremic metabolic alkalosis (HHMA), resulting from excessive electrolyte loss through sweat. This retrospective study aimed to clinically characterize individuals with cystic fibrosis who developed HHMA, characterize their CFTR genetic profile and compare it with that of other individuals with cystic fibrosis followed at a Brazilian tertiary referral center, and contextualize these findings within the available national and international literature. Among 257 individuals with cystic fibrosis followed at a tertiary referral center between 2014 and 2024, 41 (15.9%) developed HHMA. Most patients were male (29; 70.7%), the median age at the first episode was approximately four months, and episodes occurred predominantly during summer. The biochemical profile was characterized by metabolic alkalosis, hyponatremia, hypokalemia, and hypochloremia. The F508del variant was the most common allele [F508del homozygous, 9 (22.0%); F508del heterozygous, 21 (51.2%); without the F508del variant, 11 (26.8%)], particularly among patients with recurrent episodes, which occurred in 9/11 (81.8%) cases. The most frequent clinical manifestations were dehydration, cough, and vomiting, although some patients presented with minimal symptoms. Management primarily consisted of intravenous and oral hydration, electrolyte replacement, and antibiotic therapy when indicated, with no HHMA-related deaths observed. The characterization of the CFTR genetic profile and its comparison with the broader cystic fibrosis population followed at the reference center provide additional insights into the genetic background of HHMA in a genetically diverse population. Taken together with findings from the national and international literature, these results indicate that HHMA is a relatively frequent and potentially recurrent complication of cystic fibrosis, particularly during early life, and may be influenced by both genetic and environmental factors. Early recognition, systematic electrolyte monitoring, and appropriate salt and fluid replacement may prevent severe complications and improve clinical management.